The effect of using the Quizizz application in mathematics learning on student learning outcomes - Muhamad Rifqi Maulana; Samsul Pahmi; Fitria Nurulaeni; Jeanne Sauce (Universitas Sarjanawiyata Tamansiswa, 2023)
This research is motivated by the need for more media use in mathematics learning. One of the impacts of the lack of media on learning mathematics is learning outcomes that could be more optimal. The media that can be used is technology, namely learning media based on the Quizziz application. The population of this study was students of SDN Dewi Sartika CBM, with the sample used being class 5 A of 35 people. Sampling using a purposive sampling technique. This study aims to determine how using the Quizziz application in learning mathematics affects student learning outcomes. The data collection techniques used were interviews, tests, and questionnaires. The data analysis tests carried out in this study were the Validity Test, Reliability Test, Normality Test, T-test, and N-Gain Test. The results of the data analysis showed that the data values were normally distributed with an average Pre-Test score of 31.74 in the less category and an average Post-Test score of 66.37 in the less category. The results of the analysis of data testing through SPSS can be seen in the Coefficients value obtained by sig. 0.000. It turns out that the value of sig. 0.000 < 0.05. It means that H0 is rejected. This shows that using the Quizizz application in learning mathematics affects student learning outcomes at SDN Dewi Sartika CBM, Sukabumi City. The N-Gain test results show that the mean value is 50.30% in the less effective category.